Generation of few-cycle laser pulses with high temporal contrast via nonlinear elliptical polarisation rotation in a hollow fibre compressor. (20th August 2019) - Khodakovskiy, N G; Kalashnikov, M P; Pajer, V; Blumenstein, A; Simon, P; Toktamis, M M; Lozano, M; Mercier, B; Cheng, Z; Nagy, T; Lopez-Martens, R
Abstract: We report on the simultaneous temporal filtering and compression of 30 fs laser pulses down to 5 fs duration via nonlinear elliptical polarization rotation (NER) in a stretched flexible hollow fibre compressor. Both the achieved 2-cycle pulse duration and the internal conversion efficiency of  ̃47% are solely limited by the applied fibre geometry. Our investigations show that precise control of the NER process could help significantly improve the temporal fidelity of high-energy hollow fibre compression schemes.